Analysis of Association of Dyspareunia in Menopausal Women with The Quality of Sexual Intercourse: Literature Review - Farizah El Husna; Ni Luh Ayu Sri Antari Putri; Eka Wahyu Dewangga; Radina Dewi Sariva Y.; Gegel Purnomo Wicaksono; Andiani Andiani (Universitas Wijaya Kusuma Surabaya, 2023)
In postmenopausal women, sexual function may worsen with increasing menopausal status. Dyspareunia is a common complaint that is experienced by women who have experienced menopause and this also causes a decrease in the quality of sexual intercourse in women who have experienced menopause. The aim of this study is to determine the relationship between dyspareunia in menopausal women and the quality of sexual intercourse. This research method uses a literature review. Literature review means reviewing various types of literature, both national journals and international journals obtained from an academic database on Google Scholar, PubMed NCBI, and Science Direct from 2013 to 2023, without language restrictions, and full-text research journals with the keywords that related between “Dyspareunia”, “Quality of Sexual Intercourse”, and “Menopause Women”. Data were obtained from twenty-two research journals that met the inclusion criteria. Results showed that overall the article supports the effect of dyspareunia in postmenopausal women on the quality of sexual intercourse. All of the 22 articles show a relationship between dyspareunia in postmenopausal women and the quality of sexual intercourse. As a conclusion, dyspareunia experienced by postmenopausal can lead to a decrease in the quality of sexual intercourse in postmenopausal women. These findings may contribute to the development of a valid association of dyspareunia in menopausal women with the quality of sexual intercourse.